Peningkatan Perilaku Hidup Bersih dan Sehat melalui Sosialisasi pada Siswa SD Inpres Kotania dan Siswa SMP BPD Kotania - Qidran A. K. Alkatiri; Deassy J.A. Hehanussa; Irfan Maajid; Ainul Qalbi; Muti’ah Paramitheya (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
Health is a fundamental right that plays a crucial role in ensuring the continuity of biological, social, and individual developmental activities. One of the efforts that can be undertaken to improve health quality is the implementation of Clean and Healthy Living Behavior (PHBS). The school environment holds a strategic role in cultivating PHBS habits, considering that school-aged children are a vulnerable group prone to various health problems due to limited knowledge about personal hygiene and disease prevention. At this developmental stage, behavior formation is strongly influenced by education, environmental examples, and daily activities within the school setting. Therefore, education and socialization about PHBS are essential steps to enhance students’ understanding, awareness, and skills in practicing healthy behaviors. The PHBS socialization activities carried out at SD Inpres Kotania and SMP BPD Kotania aim to instill a healthy lifestyle from an early age by providing learning materials, demonstrations, and hands-on practice related to clean and healthy behaviors. Through these activities, students are expected to apply PHBS independently, both at school and at home, thereby contributing to reducing the risk of disease and creating a safe and healthy learning environment. This initiative also serves as a sustainable preventive effort to improve the overall health quality of the community in the future.